2007
DOI: 10.1002/ijc.23264
|View full text |Cite
|
Sign up to set email alerts
|

Carcinogenetic impact of ADH1B and ALDH2 genes on squamous cell carcinoma risk of the esophagus with regard to the consumption of alcohol, tobacco and betel quid

Abstract: The consumption of alcohol, tobacco and betel quid has been found to be an important contributor to esophageal squamous cell carcinoma (ESCC) in Taiwan. The genotoxic effect of the ADH1B and ALDH2 genes modulating an individual's alcohol-metabolizing capacity on ESCC may be linked to drinking behavior, intake pattern and other exogenous factors. To investigate the interplay of these genetic and environmental factors in determining the risk of ESCC, a multicenter case-control study was conducted. Here, 406 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
86
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 103 publications
(89 citation statements)
references
References 42 publications
2
86
1
Order By: Relevance
“…20 Among drinkers, each additional 5-years of drinking was observed to have a 0.892-fold (12.1% reduction) decreased OR of harboring the ADH1B Arg homozygote, but down to a 0.787-fold (27.1% reduction) reduced OR of carrying the ALDH2 Lys variant. Compatible with epidemiological reports on the stronger ESCC risk for ALDH2 genetic susceptibility, 5,17 this information implies that the carcinogenetic influence of alcohol on the time of ESCC diagnosis is more dependent on the inactive ALDH2 allele than on the slowform ADH1B homozygote.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…20 Among drinkers, each additional 5-years of drinking was observed to have a 0.892-fold (12.1% reduction) decreased OR of harboring the ADH1B Arg homozygote, but down to a 0.787-fold (27.1% reduction) reduced OR of carrying the ALDH2 Lys variant. Compatible with epidemiological reports on the stronger ESCC risk for ALDH2 genetic susceptibility, 5,17 this information implies that the carcinogenetic influence of alcohol on the time of ESCC diagnosis is more dependent on the inactive ALDH2 allele than on the slowform ADH1B homozygote.…”
Section: Discussionmentioning
confidence: 68%
“…11,16 Studies in several populations have found that the risk of esophageal SCC (ESCC) is closely associated with genetic polymorphisms of the two alcohol-metabolizing genes, and this relationship has been suggested to be alcohol amount dependent. [17][18][19] Recently, the mutant ALDH2 Glu487Lys allele in molecular epidemiological studies has been reported to be more prevalent among head and neck carcinoma (HNC) patients of a younger diagnosed age (<66 years). 20 Earlier multiple esophageal dysplasias in HNC patients have also been linked to the presence of this variant allele.…”
Section: Uiccmentioning
confidence: 99%
“…Following a negative endoscopy, an efficient risk-assessment method is needed to design surveillance programs for early detection of superficial SCC in the head and neck region and esophagus (2). However, past efforts based on demographic characteristics (5-7), lifestyle risk factors (8,9), genetic susceptibilities (10)(11)(12)(13)(14), serological markers (15)(16)(17)(18), and endoscopic findings (19), alone or in combination (15,20,21), have not produced models efficient enough to be effective.…”
Section: Introductionmentioning
confidence: 99%
“…Acetaldehyde has been established as a carcinogen in experimental animals (8) and is suspected of playing a critical role in cancer development in humans (9). Case-control studies in Japanese (10)(11)(12)(13) and Taiwanese (13)(14)(15)(16) individuals and prospective studies in which esophageal iodine staining has been used in Japanese alcoholics (17)(18)(19) have consistently shown a very strong link between the risk of esophageal SCC and alcohol drinking in people possessing the ALDH2*1/*2 genotype. Alcohol drinking together with the ALDH2*1/*2 genotype has been reported to be a risk factor for multiple cancerization in the upper aerodigestive tract (13,17,(19)(20)(21) and for oropharyngolaryngeal SCC (13,18,20,22,23).…”
Section: Introductionmentioning
confidence: 99%